Scientific bases of elementary physics courseon the example of the part «Conservation laws in mechanics» - Kovel, T.S.; Ilina, L.F. (KSU Publ., 2017)
The article is devoted to the conservation laws in mechanics. In this paper, an overview of the 3 fundamental physical laws, which are important in physics is quite huge. Conservation laws hold of all the laws of nature a special position. It should be noted, however, that they are the basis for the most important calculations in physics and its technical applications, in some cases, allow to predict the effects and phenomena in the study of a variety of physical and chemical systems and processes. The conservation laws allow a relatively simple way, without considering the forces acting on the body and without motion tracking system of bodies, to solve a number of practical problems.
"Механикадағы сақталу заңдары" бөлімі мысалдарындағы элементарлы физика курсының ғылыми негіздері
Научные основы элементарного курса физики на примере раздела «Законы сохранения в механике»
Keywords: impulse; energy; angular momentum; homogeneous; isotropic; closed system; the increased complexityof the problem